Amérique Septentrionale: avec l'indication des principaux courants marins d'Amérique en Europe. - Périgot, Charles, 1828-1885 (Librairie Ch. Delagrave & Cie. Editeurs, 1870)
Map shows principal currents of the North Atlantic and North Pacific Oceans, the locations of the underwater transatlantic telegraph cables to England and France, and the route of the transcontinental railroad across the United States. Relief shown by hachures. No scale indicated.